ANALYSIS OF SUPPLY AND DEMAND OF BROILER CHICKEN MEAT IN BALI PROVINCE - Regiana Yoshika Dewantari; Nyoman Suparta; Budi Rahayu Tanama Putri (Agricultural Socio-Economics Journal, 2023)
This study aims to analyze factors such as broiler chicken population, DOC prices, feed prices and drug prices on boiler chicken meat supply, and population, per capita income, boiler chicken meat prices, tourist visits and religious holidays to demand boiler chicken meat in Bali Province. The research method used is multiple linear regression analysis with the help of the SPSS program and trend analysis. Used 2 dependent variables and 9 independent variables. The data used in this study are primary data obtained from interviews with 100 respondents, while secondary data is obtained from annual data from 2009 to 2019. The results of the study concluded that the broiler chicken population, DOC prices, feed prices and drug prices had no effect on the supply of boiler chicken meat at the 95% confidence level and R2 of 0.641. This is because most breeders have partnerships with companies. Meanwhile, partially the demand for boiler chicken meat is determined by the population with a coefficient of 0.045 at 95% confidence. This shows that the increase in population is directly proportional to the consumption of broiler chicken meat. While other variables do not affect the demand for broiler chicken in Bali Province.